THE INFLUENCE OF WEBSITE QUALITY, PRICE, AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF TOKOPEDIA E- COMMERCE (CASE STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, MALIKUSSALEH UNIVERSITY) - Fitri Faryani Manik; Halida Bahri; Ikramuddin; T. Edyansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of website quality, price, and service quality on customer satisfaction with e-commerce Tokopedia, with a case study on students of the Faculty of Economics and Business, Malikussaleh University. The research method used is a quantitative approach with purposive sampling technique involving 120 respondents. Data was collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results indicate that partially, website quality, price, and service quality have a positive and significant influence on customer satisfaction. Simultaneously, these three variables also have a significant effect on customer satisfaction, with a coefficient of determination value of 72.3%. These findings suggest that good website quality, competitive pricing, and satisfactory service are key factors in enhancing customer satisfaction with Tokopedia.